2010
DOI: 10.1088/0004-637x/719/1/642
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Cosmic Crystals in Highly Supersaturated Silicate Vapor Produced by Planetesimal Bow Shocks

Abstract: Several lines of evidence suggest that fine silicate crystals observed in primitive meteorite and interplanetary dust particles (IDPs) nucleated in a supersaturated silicate vapor followed by crystalline growth. We investigated evaporation of μm-sized silicate particles heated by a bow shock produced by a planetesimal orbiting in the gas in the early solar nebula and condensation of crystalline silicate from the vapor thus produced. Our numerical simulation of shock-wave heating showed that these μm-sized part… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 27 publications
(79 reference statements)
0
23
0
Order By: Relevance
“…The mean radius and formation rate of the sample are 10.2 nm and 1.7 Â 10 11 cm À 3 s À 1 , respectively. [20,21]. Terminal mean radius a N can be obtained from L value, which is 63.2 in present experiment, as drown by a bold broken line.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…The mean radius and formation rate of the sample are 10.2 nm and 1.7 Â 10 11 cm À 3 s À 1 , respectively. [20,21]. Terminal mean radius a N can be obtained from L value, which is 63.2 in present experiment, as drown by a bold broken line.…”
Section: Resultsmentioning
confidence: 67%
“…Since the WO 3 particles condense in a cooling stage, to treat an environment dynamically changing, a diagram based on the classical nucleation theory shown in Fig. 5 has been used [20,21]. Using this diagram, the mean terminal radius of grown particle can be determined from a supersaturation with respect to DT/T e and…”
Section: Attempt Of Classical Nucleation Theorymentioning
confidence: 99%
“…It is likely that solids will be fully or partially melted in these regions, and experience rapid cooling rates, resulting in objects that do not fit the classical definition of chondrules. For example, Miura et al (2010) proposed that silicate crystals found in meteorites could be produced by supercooling of a silicate vapor in bow shocks. Alexander et al (2007) found that the microstructure of pyroxene in interplanetary dust particles (IDPs) indicates that it formed at temperatures >1258 K and cooled relatively rapidly (∼1000 K hr −1 ), suggesting some type of shock heating.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…suggest that ferroan olivine overgrowths on chondrules and chondrule fragments are produced by cooling rates orders of magnitude greater than those experienced by the chondrules themselves. Formation outside the chondrule-forming impact parameter in a planetary embryo bow shock may explain objects such as the silicates found in meteorites (Scott & Krot 2005;Miura et al 2010), pyroxene in IDPs (Alexander et al 2007), and overgrowths on chondrules . Further detailed modeling of the thermal histories of objects formed in bow shocks around planetary embryos is necessary to address this intriguing possibility.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…dust particles evaporated near the protostar and recondensed in the bipolar outflow (Patel et al 2000) and ⁄ or evaporated by shockwave heating and recondensed behind it (Kimura et al 2008;Miura et al 2010). The results of our annealing experiments show that amorphous silicate dust has never been heated to more than 1003 K in an oxidizing atmosphere (after it recondensed from the vapor), because amorphous silicate particles quickly crystallize above this temperature.…”
Section: Astronomical Implicationsmentioning
confidence: 80%